Beyond knowledge sharing : interactions in online discussion communities - Chua, Alton Yeow Kuan (2013)
This study attempts to investigate different types of interactions in online discussion communities (ODCs). Content analysis was performed on a sample of 1,800 messages from six ODCs. The findings suggest that ODC users seemed to be engaged in a combination of online interactions to satisfy human sharing needs such as to share or acquire knowledge, establish a social presence and convey emotions. Moreover, differences could be noted in the extent to which online interactions were observed between support and technical ODCs. Support ODCs refer to relationship communities in which users receive emotional and informational support through expressions of compassion, advice and feedback for better decision making while technical ODCs refers to interest communities whose members are bound together by common interests to share insights and solutions to problems. This study serves as a springboard for researchers to study ODCs from a socio-psychological perspective with a thrust on the social and emotional needs of users and their influence on knowledge sharing. As for practitioners, they can look into creating environments for online communities to meet different sharing needs of users including domain knowledge sharing, social expression and emotional disclosure.